Bleeding assessment tools to predict von Willebrand disease: Utility of individual bleeding symptoms. Issue 1 (30th October 2019) - Spradbrow, Jordan; Letourneau, Sasha; Grabell, Julie; Liang, Yupu; Riddel, James; Hopman, Wilma; Blanchette, Victor S.; Rand, Margaret L.; Coller, Barry S.; Paterson, Andrew D.; James, Paula D.
Abstract: Background: Bleeding assessment is part of the diagnostic workup of von Willebrand disease (VWD). Bleeding assessment tools (BATs) have standardized obtaining this information but have been criticized because they are time consuming. Objective: To use our legacy data to determine which questions from BATs are the strongest predictors of a VWD diagnosis. Patients/Methods: Bleeding score data from 3 different BATs were used. Patients aged <12 years were excluded. Questions on BATs relate to different bleeding symptoms, and each symptom is scored by severity. Scores for each symptom were sorted based on whether they indicated clinically significant bleeding, and nonsignificant scores were set as the reference category. Multivariable logistic regression was used to determine the symptoms that were the strongest predictors of a laboratory‐confirmed VWD diagnosis. Results: A total of 927 participants were included; 144 (16%) were patients with VWD, and 783 (84%) were healthy controls. The top 3 symptoms for which a clinically significant positive response increased the likelihood of VWD were hemarthrosis (odds ratio [OR], 19.2; 95% confidence interval [CI], 3.7‐100.4), postsurgical bleeding (OR, 15.2; 95% CI, 5.9‐38.9), and menorrhagia (OR, 10.3; 95% CI, 4.9‐21.9). With each increase in number of bleeding symptom categories with clinically significant scores, subjects had a stepwise increase in odds of a VWD diagnosis. Conclusions: Our results suggest that most of the bleeding symptoms on BATs are significant predictors of VWD, and there is value in assessing multiple bleeding symptoms when eliciting a bleeding history. Certain bleeding symptoms are more useful predictors than others. Future BAT revisions may consider adding a relative weighting to each symptom.